Risk of Contralateral Breast Cancer in Women with Ductal Carcinoma In Situ Associated with Synchronous Ipsilateral Lobular Carcinoma In Situ - Miller, Megan E. (Ann Surg Oncol, 2019)
BACKGROUND: Lobular carcinoma in situ (LCIS) is a risk factor for breast cancer, but the effect of LCIS found in association with ductal carcinoma in situ (DCIS) is unknown. Here we compare contralateral breast cancer (CBC) and ipsilateral breast tumor recurrence (IBTR) rates among women with DCIS with or without synchronous ipsilateral LCIS treated with breast-conserving surgery (BCS). METHODS: DCIS patients undergoing BCS from 2000–2011 with a contralateral breast at risk were stratified by the presence or absence of synchronous ipsilateral LCIS with the index DCIS (DCIS+LCIS vs DCIS). Those with contralateral, bilateral, or prior ipsilateral LCIS were excluded. Associations of patient, tumor, and treatment factors with CBC and IBTR were evaluated. RESULTS: Of 1888 patients identified, 1475 (78%) had DCIS and 413 (22%) had DCIS+LCIS. At median follow-up of 7.2 years (range 0–17 years), 307 patients had a subsequent first breast event; 207 IBTR and 100 CBC. The 10-year cumulative incidence of IBTR was similar in both groups: 15.0% vs 14.2% (log-rank p=0.8) for DCIS+LCIS vs DCIS, respectively. The 10-year cumulative incidence of CBC was greater in the DCIS+LCIS group: 10.9% vs 6.1% for DCIS (log-rank p<0.001). After adjustment for other factors, CBC risk remained higher in DCIS+LCIS compared with DCIS (HR 2.06, 95% CI 1.36–3.11, p=0.001); there was no significant difference in IBTR risk. CONCLUSIONS: Compared to DCIS alone, DCIS+LCIS is associated with similar IBTR risk but double the risk of CBC. This finding should inform treatment decisions, in particular regarding endocrine therapy for risk reduction.